Demographic Factors Influencing Parental Perceptions of Early Childhood Sexual Education: A Study in Malang City - Mukhlis, Akhmad; Husen, Wahyuni; Fitriah, Nurlaeli; Elvira, Melly; Putri Santoso, Sandy Tegariyani; Rahmanto, Kelik Desta; Rochmah, Ainur (Program Studi Pendidikan Islam Anak Usia Dini, Fakultas Ilmu Tarbiyah dan Keguruan, UIN Sunan Kalijaga, Yogyakarta, 2024)
This study examines parents' perceptions of the importance of sexual education in early childhood and the demographic factors influencing these views. Using multiple regression analysis, a quantitative survey was conducted with 100 Malang City parents with children aged 4-6 years. The results show that 84% of parents held positive perceptions, while 16% expressed negative views. The F-test yielded a calculated F value of 26.6 with a significance level of 0.000 (<0.05), indicating that gender, age, and parental education significantly influence perceptions of sexual education. Parents with negative views often cited traditional beliefs about child development, considering children unprepared for topics on sexuality. Cultural factors, a lack of exposure to sexual education during their childhoods, and insufficient knowledge about appropriate content for young children further contributed to this stance. The findings suggest that sexual education for early childhood must consider comprehensive education for parents, ensuring they understand appropriate boundaries and materials. Demographic factors such as age, gender, and education must also be addressed when designing educational programs. Limitations of this study include its focus on a single city and a relatively small sample size, which may restrict the generalizability of the findings. Future research should expand the geographic scope and examine other factors, such as socioeconomic status or cultural diversity. Addressing these limitations could provide deeper insights into how to design effective sexual education programs that respect cultural contexts while fostering understanding and acceptance among parents.